Detective fiction & the african scene : from the whodunit? to the whydunit? - Asong, Linus T. (Linus Tongwo), 1947-2012 (Langaa Research & Pub., 2012)
"From its very inception, detective fiction has enjoyed a great popularity among the young and the old, the learned and the not so learned. By some unfortunate stroke of irony, its respect has not kept pace with its enormous popularity. For over half a century now, it has remained the bane of creative writing. In strict intellectual circles, it is very rare to find people talk defensively and interestingly about the genre. Yet Asong has chosen to do just that. He has stoutly defended the weak by putting up a good case for its continued existence. He has also shown how irresistible key elements of the genre are to even the best respected novelists. Finally he has demonstrated for the first time, how the genre has been domesticated by African writers of very great repute such as Ngugi, Sembene and Lessing. That he has been able to prove that these writers have used techniques of detective fiction is a significant broadening of the horizons for appreciating creative writing in Africa."--Project Muse.